2020
DOI: 10.3389/fpubh.2020.576693
|View full text |Cite
|
Sign up to set email alerts
|

Learning Processes as Key for Success in Workplace Health Promotion Interventions in Health Care

Abstract: There is limited previous research on how learning processes contribute to the outcomes of workplace health promotion (WHP) leadership interventions. The aim of this study was to identify the outcomes of a system-based WPH education program for managers and investigated what impact the intervention program had on health-oriented leadership, improvement work, and employee well-being, as well as what factors (i.e., how manager's active work following the intervention and organizational learning climate) contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Some studies found that a positive learning climate or culture was important for managers’ motivation, engagement and development as a leader (Cherkowski and Walker, 2016; Eriksson and Dellve, 2020; Rodriguez-Gomez et al , 2020). It is also believed that this is important for managers to handle their work situation (Eriksson and Dellve, 2020; Plimmer et al , 2021). In the study by Cherkowski and Walker (2016), managers’ experiences of flourishing in their work of leading schools were investigated.…”
Section: Findings Of the Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies found that a positive learning climate or culture was important for managers’ motivation, engagement and development as a leader (Cherkowski and Walker, 2016; Eriksson and Dellve, 2020; Rodriguez-Gomez et al , 2020). It is also believed that this is important for managers to handle their work situation (Eriksson and Dellve, 2020; Plimmer et al , 2021). In the study by Cherkowski and Walker (2016), managers’ experiences of flourishing in their work of leading schools were investigated.…”
Section: Findings Of the Reviewmentioning
confidence: 99%
“…Organizational learning climate and how managers’ active work and learning process contributed to the results of a health-promoting leadership intervention were investigated in the study by Eriksson and Dellve (2020). The results showed that managers took on different assignments in the program differently, indicating that interventions and training programs need to be customized for each organization.…”
Section: Findings Of the Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, these articles establish that leaders and leadership styles influence employee (or pupils') health. Whereas a number of these articles conclude that leadership affects employee or workplace health in general [59,64,65,28,73], others are meant to explain what types of leadership are beneficial to health in the workplace. On the one hand, three articles covered transformational leadership's effects, concluded that this leadership type is suitable for countering bullying in the workplace [38], and contributed to an optimal effort-reward balance [61].…”
Section: Leadership's Role In Employee Healthmentioning
confidence: 99%
“…The development of sustainable quality of work and work efficiency has also been highlighted as a process that promotes the development of individuals’ and organizations’ resources and resilience to dealing with different forms of work demands [ 4 , 13 ]. It has, in this context, been emphasized that the development of sustainable work requires a learning climate for developmental work, including a social team climate that promotes collaboration on work improvements [ 14 ]. This study thus includes, as explanatory factors, how digital resources, including DMSs, and a digital learning climate may contribute to or hinder outcomes related to sustainable work when working remotely.…”
Section: Introductionmentioning
confidence: 99%